(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The aim of this research is to identify the level of application of human talent management strategies in the College of Economics - Al Khums / University of Al-Marqab, and to know the level of organizational creativity, the level of organizational creativity in the college under discussion, and to identify the impact of applying human talent management strategies represented in (attracting and attracting talent, developing talent, Retention of the gifted) on the organizational creativity of the faculty members in the college under study, and the research relied on the descriptive approach, targeting all the permanent faculty members of the Faculty of Economics - Al-Khums / Al-Marqab University, who taught during the semester (Spring 2022 AD), and their number is ( 83) a faculty member, and to achieve the objectives of the research, a questionnaire was designed for the purpose of collecting primary data and distributed to a sample consisting of (68) faculty members, and the spss statistical program was used to analyze the research data, and the research results showed that there is a weak level of application of management strategies Human talents in their dimensions (strategy of attracting and attracting talents, talent development strategy, talent retention strategy) in the college under study. The results also showed that there is a medium level of organizational creativity in the college. The level of organizational creativity in the college under study.